1993
DOI: 10.1002/cne.903270109
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors in the avian brain: Survey reveals general distribution and forebrain areas unique to songbirds

Abstract: Estrogens play an important role in the control and differentiation of species-typical behavior and in endocrine homeostasis of birds, but the distribution and evolution of cells that contain estrogen receptors in the avian brain are poorly understood. This study therefore surveys 26 species in the avian orders Anseriformes (1 species), Galliformes (2), Columbiformes (3), Psittaciformes (1), Apodiformes (2), and Passeriformes (3 suboscines, 14 oscines). Indirect immunocytochemistry with the estrogen receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
187
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(204 citation statements)
references
References 41 publications
16
187
1
Order By: Relevance
“…Similarly, ER␣ are expressed in HVC (including the caudomedial portion) but are not found in the surrounding nidopallium in every songbird species studied to date, including whitecrowned sparrows (Gahr et al, 1993;Bernard et al, 1999;Metzdorf et al, 1999;Fusani et al, 2000); ER␤ mRNA has been found in caudomedial nidopallium of starlings but is not present in the song nuclei (Bernard et al, 1999). Unlike some songbird species, ERs are expressed only sparsely in the arcopallium dorsal to RA in white-crowned sparrows (Gahr et al, 1993).…”
Section: Osmotic Pump and Intracerebral Infusions Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, ER␣ are expressed in HVC (including the caudomedial portion) but are not found in the surrounding nidopallium in every songbird species studied to date, including whitecrowned sparrows (Gahr et al, 1993;Bernard et al, 1999;Metzdorf et al, 1999;Fusani et al, 2000); ER␤ mRNA has been found in caudomedial nidopallium of starlings but is not present in the song nuclei (Bernard et al, 1999). Unlike some songbird species, ERs are expressed only sparsely in the arcopallium dorsal to RA in white-crowned sparrows (Gahr et al, 1993).…”
Section: Osmotic Pump and Intracerebral Infusions Surgerymentioning
confidence: 99%
“…Song learning, adult song behavior, and the underlying neural circuit are sensitive to sex steroids, and steroid receptors or their mRNA are present in all of the major song nuclei (see Fig. 1 A) (Arnold et al, 1976;Gahr et al, 1993;Nastiuk and Clayton, 1995;Smith et al, 1996;Bernard et al, 1999;Metzdorf et al, 1999;Soma et al, 1999b;Fusani et al, 2000;Kim et al, 2004). In seasonally breeding songbirds, there are pronounced hormone-driven seasonal changes in volume and neural morphology of song nuclei, which are accompanied by changes in stereotypy, duration, and production rate of song (Nottebohm, 1981;Ball et al, 2004;Brenowitz, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have focused on the HVC because it is the first song control nucleus to grow in response to elevated systemic T , and because it expresses estrogen receptors (ER) (Figure 1; Gahr et al, 1993;Bernard et al, 1999;Metzdorf et al, 1999;Fusani et al, 2000). Androgen receptors (AR) or their mRNA are expressed in every song control nucleus and the syrinx, the avian vocal organ (Fig 1; Arnold et al, 1976;Gahr et al, 1993;Nastiuk and Clayton, 1995;Smith et al, 1996;Bernard et al, 1999;Metzdorf et al, 1999;Soma et al, 1999b;Fusani et al, 2000;Kim et al, 2004). AR immunoreactivity is elevated in the HVC of Gambel's white-crowned sparrows captured in the spring; AR immunoreactivity in other song control nuclei was not quantified (Soma et al, 1999b).…”
Section: Mechanisms Of Growth Photoperiod Increases Plasma T Levelmentioning
confidence: 99%
“…Andrews, 1991;Cynx and Nottebohm, 1992), and the neuroendocrine mechanisms underlying these processes are beginning to be revealed. For example, androgen and oestrogen receptors and aromatase activity have been detected in the hippocampus of mammals and birds (Gahr et al, 1993;Kerr et al, 1995;Weiland et al, 1997;Saldanha et al, 1999), a brain area known to be involved in relational memory processes (e.g. declarative memory, Eichenbaum et al, 1992;Squire, 1992).…”
Section: The Adaptive Value Of Androgen Social Modulation: Androgens mentioning
confidence: 99%